Mental workload and visual impairment: differences between pupil, blink, and subjective rating - Pérez, Elisa; Nunes, Luis Miguel; Conchillo, Ángela; Recarte, Miguel Ángel (The Spanish Journal of Psychology, 2008)
This research has two aims: (a) To study the concurrent validity of three measures of mental workload, NASA TLX rating scale, pupil dilation and blink rate, testing the hypothesis that they will provide convergent results using a single-task, and dissociative results for dual-task; and (b) To analyse their capability to predict visual search impairment. These three measures were analyzed in the same cognitive tasks in singletask and dual-task (cognitive task and visual search) conditions in a within-subjects experiment with twenty-nine participants. Mental workload measures showed concurrent validity under single-task condition, but a complex pattern of results arose in the dualtask condition: it is suggested that NASA TLX would be a subjective addition of the rating of each task; pupil dilation would measure the average arousal underlying the cognitive tasks; and the blink rate would produce opposite effects: whereas mental workload of cognitive tasks would increase blink rate, visual demand would inhibit it. All three measures were good predictors of visual impairment. The soundness of these measures is discussed with regard to the applied field of driving and other activities.